Electric Cell-Substrate Impedance Sensing and Cancer Metastasis - Jiang, Wen G.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
Cell based impedance sensing is becoming a new biophysical and cellular technology in cell based analyses. The technology has been used in investigation of cellular growth and death, cell adhesion and migration, cell invasion and cell-cell interactions, cell toxicity, angiogenesis, cell permeability, signal transduction and cellular behaviour under flow conditions. It is a probe free, highly sensitive, and versatile technology platform. Recent development in the technology has also allowed high throughput, automated analyses. It has been widely explored in chemistry, toxicity, cell biology, cancer biology, and other areas of chemistry, medicinal chemistry, life and medical science. Written by experts in the area of cell impedance sensing, including the Nobel Laureate Dr Ivar Giaever, this books covers the background of electric cell-substrate impedance sensing, their applications in cell based investigations, particularly in the area of cancer biology. This book is the first on this technology platform and will be a highly useful reference for molecular and cell biologists, cancer biologists, chemists and biochemists, clinical researchers who work in the areas of cell biology, molecular biology, toxicology, pharmaceutical industry, life science and medical research.
Keywords: Medicine; Oncology; Biomedicine; Cancer Research; Biomedicine general; Molecular Medicine; Oncology